Analisis Konten Buku Ajar Bahasa Arab Sang Pangeran Nahwu Al-Ajurumiyyah - M Alaika Nasrulloh; Imamatul Mufidah (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
The book of Sang Pangeran Nahwu Al-Ajurumiyah is an introductory book to the Kitab al Ajurumiyah written in Indonesian. This book is not a translation of the original book, but rather a translation like the interpretation of the Qur'an. This book is suitable for non-Arabic students, especially those in Indonesia who are still predicated as beginners in learning Arabic. This type of research is library research with a qualitative approach. The data collection technique uses documentation. And the results of this study indicate that the book Sang Pangeran Nahwu Al-Ajurumiyah has met the criteria of a good textbook in terms of material, which is in accordance with the scientific theoretical basis according to Masnur Muslich, including material accuracy, material coverage, and material support. Then in terms of scientific theory according to Ali al Qosimiy, this book is suitable in basic material but in the layout of the basic material it is not appropriate, and has met the criteria in terms of supporting material and special material. Meanwhile, in the stage of presenting the material, the book has not yet reached conformity with the selection and repetition stages. However, it has reached conformity to the gradation and repetition stages.